A metabolite roadmap of the wood‐forming tissue in Populus tremula. Issue 5 (27th August 2020) - Abreu, Ilka N.; Johansson, Annika I.; Sokołowska, Katarzyna; Niittylä, Totte; Sundberg, Björn; Hvidsten, Torgeir R.; Street, Nathaniel R.; Moritz, Thomas
Summary: Wood, or secondary xylem, is the product of xylogenesis, a developmental process that begins with the proliferation of cambial derivatives and ends with mature xylem fibers and vessels with lignified secondary cell walls. Fully mature xylem has undergone a series of cellular processes, including cell division, cell expansion, secondary wall formation, lignification and programmed cell death. A complex network of interactions between transcriptional regulators and signal transduction pathways controls wood formation. However, the role of metabolites during this developmental process has not been comprehensively characterized. To evaluate the role of metabolites during wood formation, we performed a high spatial resolution metabolomics study of the wood‐forming zone of Populus tremula, including laser dissected aspen ray and fiber cells. We show that metabolites show specific patterns within the wood‐forming zone, following the differentiation process from cell division to cell death. The data from profiled laser dissected aspen ray and fiber cells suggests that these two cell types host distinctly different metabolic processes. Furthermore, by integrating previously published transcriptomic and proteomic profiles generated from the same trees, we provide an integrative picture of molecular processes, for example, deamination of phenylalanine during lignification is of critical importance for nitrogen metabolism during wood formation.